1971
DOI: 10.1002/star.19710230108
|View full text |Cite
|
Sign up to set email alerts
|

Damaged Starch Determination in Wheat Flours in Relation to Dough Water Absorption

Abstract: Four methods (three enzymatic and one non‐enzymatic) for damaged starch determination have been applied to 51 flours of known moisture and protein contents and known water absorption. The three enzyme methods for damaged starch give results in substantial agreement and in conjunction with the other parameters predict dough water absorption by multiple regression equations more closely than does a colorimetric method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…The association between damaged starch and protein contents was poor, the correlation coefficients being statistically non-significant (Table 3). Similar correlations were obtained by Tara and Bains [ll] in respect to 46 Indian commercial flours from wheats imported from the U.S. Dodds [13] reported significant positive correlation coefficients varying from 0.47 to 0.56 and 0.52 to 0.65 for two separate series From the error standard deviations (ESD) of absorption predicted from regressions (Table 4), the Stewart method Table 5 regarding the coefficients of protein which varied…”
Section: Resultssupporting
confidence: 80%
“…The association between damaged starch and protein contents was poor, the correlation coefficients being statistically non-significant (Table 3). Similar correlations were obtained by Tara and Bains [ll] in respect to 46 Indian commercial flours from wheats imported from the U.S. Dodds [13] reported significant positive correlation coefficients varying from 0.47 to 0.56 and 0.52 to 0.65 for two separate series From the error standard deviations (ESD) of absorption predicted from regressions (Table 4), the Stewart method Table 5 regarding the coefficients of protein which varied…”
Section: Resultssupporting
confidence: 80%
“…Accompanying the increased granule swelling is an increase in starch polymer molecule solubility and an increase in susceptibility of the damaged starch granules to the action of amylases. In fact, early methods for determination of the relative amounts of damaged starch in samples were based on measurements of solubilized AM or susceptibility to hydrolysis by α-amylase (Alsberg & Griffing 1925, Pulkki 1938, Jones 1940, Sandstedt & Mattern 1960, Williams & LeSeeleur 1970, Dodds 1971, Evers et al 1984a), but Evers et al (1984b) determined that the two parameters were independent of each other. Tamaki et al (1997aTamaki et al ( , 1998 also found increases in susceptibility of damaged starch granules to the action of amylases.…”
Section: Effects On Starch Characteristicsmentioning
confidence: 99%
“…Farrand, 1969;Dodds, 1971) but it is still common practice to make a 'direct' measurement based on assessment of fl our performance in some form of dough mixing test. The basis of such tests is to mix a dough and measure aspects of its rheology, either during mixing or afterwards.…”
Section: The Water Absorption Capacity Of Fl Ourmentioning
confidence: 98%